Aplicación de una dieta enriquecida con biomasa de microalgas como fuente de prebióticos en pollos broiler - Rodríguez Ovallos, Jessica (2021)
The world's population is increasingly demanding nutritious food, currently the main source of dietary protein, at least in developing countries, it is animal production. Therefore, it is necessary to implement biotechnological processes to meet the needs of the population, have a better treatment of animals, and preserve the resources. Consequently, a diet enriched with microalgae as a growth promoter in broiler chickens was evaluated. Sixty broiler chickens, 1 day, of the cobb500 line were used, divided into four study groups consisting of 12 chickens each. The treatments received balanced feed and were differentiated by the addition of the microalgae used: T0 (control), T1 (Isochyrisis galbana), T2 (Tetraselmis Suecica), T3 (Porphyridium), T4 (all algae mixed). The percentage of microalgae that was added to the feed was manually mixed at 2% with the amount of daily feed consumption of chickens respectively. An analysis of variance (ANOVA) was used to interpret the experimental results obtained. The daily weight gain was significantly higher in T2 (Tetraselmis Suecica) than the control in 7 of the 30 days of breeding, which suggests that this alga is a considerable alternative for poultry industries as with this they can produce more chicken meat in less time, and without any use antimicrobials which may generate an adverse effect on consumers.